The game plan: Using gamification strategies to engage learners as active players (Journal of Applied Learning and Teaching, 2019)
The modern learner is a different and unique individual. Impatient, fast-acting and competitive, learners today are hungry and passionate, but also demand a more interactive approach to education. A Talent LMS survey showed that over 80% of learners wished their learning journeys were more interactive (Apostolopoulos, 2019). This article on gamification focuses on the strategic use of game mechanics and features to enhance learning capabilities and retention rates of learners, with references to modern game and real-world examples.Techniques and tips on evolving workplace learning practices and growing an ecosystem of self-directed learning are described. Additionally, this paper explores the rise of the gig economy and new generation professionals, harnessing gamification as an effective tool to allow individuals to develop and build their skill sets and strengths. Pick up useful strategies on crafting a personal learning profile, and how we can evolve as learners though gamification! Game on!